Cell membrane-biomimetic coating via click-mediated liposome fusion for mitigating the foreign-body reaction. (April 2021) - Yang, Lingbing; Lin, Xubo; Zhou, Jin; Hou, Sen; Fang, Yunnan; Bi, Xuewei; Yang, Li; Li, Linhao; Fan, Yubo
Abstract: The foreign-body reaction (FBR) caused by the implantation of synthetic polymer scaffolds seriously affects tissue-biomaterial integration and tissue repair. To address this issue, we developed a cell membrane-biomimetic coating formed by "click"-mediated liposome immobilization and fusion on the surface of electrospun fibers to mitigate the FBR. Utilization of electrospun polystyrene microfibrous scaffold as a model matrix, we deposited azide-incorporated silk fibroin on the surface of the fibers by the layer-by-layer assembly, finally, covalently modified with clickable liposomes via copper-free SPAAC click reaction. Compared with physical adsorption, liposomes click covalently binding can quickly fuse to form lipid film and maintain fluidity, which also improved liposome stability in vitro and in vivo . Molecular dynamics simulation proved that "click" improves the binding rate and strength of liposome to silk substrate. Importantly, histological observation and in vivo fluorescent probes imaging showed that liposome-functionalized electrospun fibers had negligible characteristics of the FBR and were accompanied by many infiltrated host cells and new blood vessels. We believe that the promotion of macrophage polarization toward a pro-regenerative phenotype plays an important role in vascularization. This bioinspired strategy paves the way for utilizing cell membrane biomimetic coating to resist the FBR and promote tissue-scaffold integration.